1991
DOI: 10.1103/physrevlett.66.1737
|View full text |Cite
|
Sign up to set email alerts
|

Negative charge state of theDXcenter inAlxGa1

Abstract: We present experimental data for the thermally activated capture of electrons on Si-induced impurity states in Al x Gaix As in the strong-lattice-relaxation regime {DX centers). Experiments have been performed after photoionization in the region of transition from the normal to the metastable state of the defect, using hydrostatic pressure up to 8 kbar. An analysis of the isothermal as well as the thermostimulated capture kinetics strongly supports the hypothesis of the negative charge state of the DX center.P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Silicon impurity in GaAs as well as in AlGaAs seems to be the negative charge state responsible for the deep donor, which leads to a negative-U behavior. [9][10][11] However, low dimensional systems like Si-␦-doped GaAs have been shown that both neutral (DX 0 ), and charged (DX Ϫ ) DX-center models, contribute to the measured mobility changes. 12 In this letter we determined the microscopic mechanism of the formation of DX centers in GaAs/Si-␦/AlAs heterostructure.…”
mentioning
confidence: 99%
“…Silicon impurity in GaAs as well as in AlGaAs seems to be the negative charge state responsible for the deep donor, which leads to a negative-U behavior. [9][10][11] However, low dimensional systems like Si-␦-doped GaAs have been shown that both neutral (DX 0 ), and charged (DX Ϫ ) DX-center models, contribute to the measured mobility changes. 12 In this letter we determined the microscopic mechanism of the formation of DX centers in GaAs/Si-␦/AlAs heterostructure.…”
mentioning
confidence: 99%
“…Jantsch et al [23,32] showed that the barrier height per one electron is two times smaller than the barrier per capture or emission event. Mosser et al [33] measured directly the capture efficiency showing that the capture energy varies with two Fermi energies during the capture transients. Both experiments were done for Si doped AlGaAs.…”
Section: Capture Processmentioning
confidence: 99%